MANAGEMENT OF PANCASILA AND CITIZENSHIP EDUCATION IN THE PREVENTION AND HANDLING OF RADICALISM AND TERRORISM IN THE STATE DEFENSE SYSTEM - Mukhtadi Mukhtadi; Arief Prayitno; Arief Rachman; Putra Sang Fajar El Harry (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2022)
Radicalism and terrorism have become a world problem including in Indonesia and become a serious threat to the country's defense system, there are need are global cooperation in the handling of radicalism and terrorism. Indonesia based on Law No. 20 of 2003 Article 37 paragraphs (1) and (2) on the National Education System mentions that Citizenship Education must be contained in the basic education curriculum, secondary education, and higher education. This research aims to find out, how is the prevention and handling of radicalism and terrorism in Indonesia and how is the management strategy of Pancasila, and Citizenship Education in the prevention and handling  radicalism and terrorism in Indonesia.  This study uses a combination research method, of digging data with questionnaires distributed through a google form, and links shared through email messaging facilities and WhatsApp in a chain. The survey was conducted to see how Pancasila and Citizenship Education play on radicalism and terrorism and to explore data from various sources, documents, and journals related to the research focus. The results of the study showed that Pancasila and Citizenship Education played a significant role in the prevention and countermeasures of radicalism, terrorism reached 99%.   The results of this study are expected to be one of the input materials for the relevant parties in taking policies on strategies to prevent and deal with radicalism and terrorism. It also encourages the involvement of the world of education and society towards Pancasila and Citizenship education and implements it in the life of the nation and state.